Canine induced pluripotent stem cell maintenance under feeder‐free and chemically‐defined conditions. Issue 6 (19th May 2021) - Kimura, Kazuto; Tsukamoto, Masaya; Yoshida, Takumi; Tanaka, Miyuu; Kuwamura, Mitsuru; Ohtaka, Manami; Nishimura, Ken; Nakanishi, Mahito; Sugiura, Kikuya; Hatoya, Shingo
Abstract: Canine induced pluripotent stem cells (ciPSCs) provide a platform for regenerative veterinary medicine, disease modeling, and drug discovery. However, in the conventional method, ciPSCs are maintained using chemically‐undefined media containing unknown animal components under on‐murine embryonic fibroblast feeder conditions, which were reported to modify cell surface of iPSCs and increases the risk of immune rejection when the cells are transplanted into patients. Moreover, in the conventional method, ciPSCs are mechanically passaged, which requires much time and effort. Therefore, the large‐scale expansion of ciPSCs is difficult, which should be resolved for using ciPSCs in clinical application and research. Here, it was shown that StemFit® AK02N and iMatrix‐511 could maintain the pluripotency of ciPSCs using conventional culture method. Furthermore, it was demonstrated that the feeder‐free and chemically‐defined ciPSC culture systems using StemFit® AK02N and iMatrix‐511 could stably maintain and allow the easy expansion of ciPSCs generated using N2B27 and StemFit® AK02N, without causing karyotype abnormalities. ciPSCs expressed several pluripotency markers and formed teratomas, including cells derived from three germ layers. Graphical abstract: We identified the feeder‐free and chemically‐defined culture system of canine induced pluripotent stem cells (ciPSCs) using StemFit® AK02N and iMatrix‐511, which is the human iPSCs medium and the recombinant laminin‐511 E8 fragment. The new culture system could stably maintain and allow the easy expansion of high‐quality ciPSCs.